2014
DOI: 10.1021/am504507w
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Thermopower Wave in Novel ZnO Nanostructures/Fuel Composite

Abstract: Thermopower wave is a new concept of energy conversion from chemical to thermal to electrical energy, produced from the chemical reaction in well-designed hybrid structures between nanomaterials and combustible fuels. The enhancement and optimization of energy generation is essential to make it useful for future applications. In this study, we demonstrate that simple solution-based synthesized zinc oxide (ZnO) nanostructures, such as nanorods and nanoparticles are capable of generating high output voltage from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 29 publications
0
36
1
Order By: Relevance
“…The 180 °C lower temperature in this case might have been due to the fast decomposition and heat loss, which were induced by the absence of Co x O y –ZnO films. On the other hand, the temperature of only the ZnO/fuel films was about 870 °C in diverse structures . The Co 3 O 4 –ZnO multipod/fuel composite films produced a higher maximum temperature probably because the released oxygen from the phase transition from Co 3 O 4 –ZnO to CoO–ZnO 1− x was supplied to the chemical reaction in the combustion waves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 180 °C lower temperature in this case might have been due to the fast decomposition and heat loss, which were induced by the absence of Co x O y –ZnO films. On the other hand, the temperature of only the ZnO/fuel films was about 870 °C in diverse structures . The Co 3 O 4 –ZnO multipod/fuel composite films produced a higher maximum temperature probably because the released oxygen from the phase transition from Co 3 O 4 –ZnO to CoO–ZnO 1− x was supplied to the chemical reaction in the combustion waves.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the temperature of only the ZnO/fuel fi lms was about 870 °C in diverse structures. [ 23 ] The Co 3 O 4 -ZnO multipod/fuel composite fi lms produced a higher maximum temperature probably because the released oxygen from the phase transition from Co 3 O 4 -ZnO to CoO-ZnO 1− x was supplied to the chemical reaction in the combustion waves. The measured surface temperature was mostly in the range of 600 °C-1000 °C, indicating a chemical transition caused by the release of oxygen molecules (R3), as measured by TGA (Figure 7 a).…”
Section: Thermopower Waves In Hybrid Composites Of Chemical Fuel/co Xmentioning
confidence: 99%
“…Lee et al. recently demonstrated that ZnO nanostructures, such as nanorods and nanoparticles are capable of generating high‐output voltage (3 V) from thermopower waves (i.e., the energy conversion from chemical energy to thermal energy which in turn converted to electrical energy) (). Athauda et al.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that ZnO nanostructures, such as nanorods and nanoparticles are capable of generating high-output voltage (∼3 V) from thermopower waves (i.e., the energy conversion from chemical energy to thermal energy which in turn converted to electrical energy) [9]. Athauda et al reported that the one-dimensional hierarchical composite materials based on ZnO nanowires and electrospun blend nanofibers can act like highly effective photocatalysts [10].…”
mentioning
confidence: 99%
“…Materials with greater Seebeck coefficients were investigated as substrates because the low Seebeck coefficient (≈80 µV K −1 ) of MWNTs was regarded as a hurdle to increase electrical potential of thermopower waves . These include Bi 2 Te 3 (≈−287 µV K −1 ), Sb 2 Te 3 (≈243 µV K −1 ), ZnO (≈−360 µV K −1 ), MnO 2 (≈−1900 µV K −1 ), and Cu–CuO–Cu 2 O powders (≈10 000 µV K −1 ) . The effect of chemical composition of fuel on thermopower waves was also explored .…”
mentioning
confidence: 99%